Development of Android-Based Application for Prayers and Dhikrs Before Sleep - Che Hariff, Mohamad Ashraf; Suhaila Sari; Nik Shahidah Afifi Md Taujuddin; Hazli Roslan; Mohd Norzali Haji Mohd; Nan Mad Sahar (Evolution in Electrical and Electronic Engineering, 2022)
Lack of sleep will affect life and may cause limitations in the capability to study and concentrate on the study, trouble attending early class, moodiness, and health problems. Mobile gadgets, especially mobile phones, can be utilized in Islamic rituals. Some applications in the Playstore or IOS store do not have bedtime prayers and dhikrs in one application. Most related websites do not feature audio files for prayers and dhikrs. The source from YouTube usually has a long version of the recital and it also has advertisements that may cause interruptions or cause the listener to sleep before finishing the prayer recital. Some recent mobile dhikrs and prayer applications may not really offer specific prayers and dhikrs for bedtime. Recently, an Android application that provides a system for users in one application for prayer and dhikrs before sleep has been developed. The project in this study provides audio and visual contents with display, playback and timer functions for prayers and dhikrs before sleep application. This study utilizes several software; Adobe Illustrator, Visual Studio Code, Node Module, Expo, and React Native Framework. The performance assessment questionnaire data demonstrates that most of the respondents are satisfied with the recital audio (68.4% found that the function is extremely good and 31.6% responded as very good). Moreover, most of the users are satisfied playback mode and timer mode of the applications (84.2% found the function extremely helpful). Furthermore, most respondents indicated that the application is user-friendly (94.5% found it is very and extremely user-friendly). Finally, in terms of quality sleep, 72.7% of respondents found that their quality sleep improved (to very and extremely good) after practicing prayer and dhikrs in this application.